Balance de mercurio en celdas electrolíticas - Maggio, Guillermo Eduardo; Guillen, Ricardo José; Rey, Silvio Enrique; Kopp, Ursula Irene; Graiño, Jorge Guillermo; Gómez, Héctor Rodolfo (Comisión Nacional de Energía Atómica; Argentina, 1983)
Fil: Maggio, Guillermo Eduardo Comisión Nacional de Energía Atómica; Argentina